Positive Influence of Role Ambiguity on JD-R Motivational Process: The Moderating Effect of Performance Recognition - Martínez-Díaz, Ana; Mañas-Rodríguez, Miguel Ángel; Díaz-Fúnez, Pedro Antonio; Limbert, Caroline (Frontiers in Psychology, 2020)
Most previous research has shown the negative influence of role ambiguity on employes’ motivational process. This has led to role ambiguity being perceived as a main hindrance demand in the workplace, with a negative effect on the Job Demands Resources (JD-R) model’s motivational process. Recent theories propose that job demands can be perceived by employes as a challenge, rather than a hindrance. However, there is little evidence on which elements of the organizational context shape this perception. The objective of this study is to elucidate the possible effect of performance recognition from the team leader on employes’ interpretation of role ambiguity as a hindrance or a challenge. Data were obtained from 706 employes of a multinational company headquartered in Almería, Spain. Results confirmed that performance recognition moderates the effects of role ambiguity: specifically, performance recognition changes the effect of role ambiguity on engagement from negative to positive and reduces role ambiguity’s negative influence on extra-role behaviors.